Thermo-sensitive Sacrificial Microsphere-based Bioink for Centimeter-scale Tissue with Angiogenesis - Xie, Mingjun; Sun, Yuan; Wang, Ji; Fu, Zhenliang; Pan, Lei; Chen, Zichen; Fu, Jianzhong; He, Yong (International journal of bioprinting, 2022)
Centimeter-scale tissue with angiogenesis has become more and more significant in organ regeneration and drug screening. However, traditional bioink has obvious limitations such as balance of nutrient supporting, printability, and vascularization. Here, with "secondary bioprinting" of printed microspheres, an innovative bioink system was proposed, in which the thermo-crosslinked sacrificial gelatin microspheres encapsulating human umbilical vein endothelial cells (HUVECs) printed by electrospraying serve as auxiliary component while gelatin methacryloyl precursor solution mixed with subject cells serve as subject component. Benefiting from the reversible thermo-crosslinking feature, gelatin microspheres would experience solid-liquid conversion during 37°C culturing and form controllable porous nutrient network for promoting the nutrient/oxygen delivery in large-scale tissue and accelerate the functionalization of the encapsulated cells. Meanwhile, the encapsulated HUVECs would be released and attach to the pore boundary, which would further form three-dimensional vessel network inside the tissue with suitable inducing conditions. As an example, vascularized breast tumor tissue over 1 cm was successfully built and the HUVECs showed obvious sprout inside, which indicate the great potential of this bioink system in various biomedical applications.